The Impact of Weblogs on Contemporary Pedagogy: Rss Feeds as an Example - Amarin, Nidal; Habashneh, Khaldoun (DIRASAT: EDUCATIONAL SCIENCES, 2019)
The study aimed to investigate how Rich Site Summary (RSS) feeds can describe weblogs on contemporary pedagogy, and how to integrate these into a single simplified representation of the organizational knowledge. To achieve the goals of the study, it adopted qualitative approach. Therefore, the research discussed the characteristics of RSS feeds search service. The results indicated that maintain student engagement outside the traditional classroom environment. Ensuring that they receive the intended feedback in time can be a challenging issue. Therefore, RSS architecture provided the students with the opportunity to share information with their peers, professors, and their real-world clients.